The achievement of Hans Urs von Balthasar: an introduction to his trilogy - Levering, Matthew (The Catholic University of America Press, 2019)
Theological aesthetics: a Kantian critique of Kant -- Theo-drama: a Hegelian critique of Hegel -- Theo-logic: a Nietzschean critique of Nietzsche.